Fear of missing out? Linking workplace changes and presenteeism. Issue 4 (21st October 2021) - Wynen, Jan; Boon, Jan; Op de Beeck, Sophie
Abstract : Abstract: Why do employees continue to work during illness? So‐called presenteeism behaviour is a topic of great managerial and societal importance as it is connected to a series of negative individual and organisational outcomes. A growing body of research points to the importance of workplace factors in shaping employee stress and uncertainty and, ultimately, presenteeism behaviour. Curiously though, the impact of workplace changes on presenteeism behaviour has not been examined, even though the potential stress‐inducing effects of such change are well‐recognised. Building on a data set from the Australian Public Service, we examine how workplace changes are related to presenteeism behaviour. Our findings show that workplace changes generally provoke presenteeism behaviour. Specifically, cutback‐related changes appear to cause presenteeism. This finding is relevant in times when many organisations are confronted with major budget cuts. Brief summary: This article explores the link between working during illness, or presenteeism behaviour, and workplace changes. Presenteeism behaviour is a topic of great managerial and societal importance as it is connected to a series of negative individual and organisational outcomes. A growing body of research points to the importance of workplace factors in shaping employee stress and uncertainty and, ultimately, presenteeism behaviour. Curiously though, the impact of workplace changes on presenteeism behaviour has not been examined, even though the potential stress‐inducing effects of such change are well‐recognised. Building on a data set from the Australian Public Service, we examine how workplace changes are related to presenteeism behaviour. Our findings show that workplace changes generally provoke presenteeism behaviour. Specifically, cutback‐related changes appear to cause presenteeism. This finding is relevant in times when many organisations are confronted with major budget cuts. Employees who experience workplace changes are more likely to go to work sick. Decreased staffing (cutback‐related change) is the main driver of presenteeism behaviour. Presenteeism is higher among employees working harder and longer hours – that is performing overtime, likely for the purpose of meeting high job demands. Fairness of pay reduces the likelihood of presenteeism. The findings suggest that although change itself is unavoidable and even necessary for organisations adapting to external demands, the potentially negative effects of change may be mitigated by appropriate change management and structures. Abstract : How do street‐level bureaucrats behave when the policies they must implement are inconsistent with their collective moral values? What dilemmas do they experience, and how do they address them? We explore these questions using the case of Arab civics teachers in Arab schools in Israel. Our findings contribute to the existing literature by emphasizing the importance of the organizational context.